TAVI Using a Self-Expandable Device for Aortic Regurgitation Following LVAD Implantation - Harun Sarwari; Andreas Schaefer; Markus J. Barten; Lenard Conradi (The Thoracic & Cardiovascular Surgeon Reports, 2019)
Background In patients treated by left ventricular assist device (LVAD), aortic regurgitation (AR) may occur. Secondary surgery to correct AR is considered high risk. Case Description We report a case of severe AR following LVAD implantation in a patient who was subsequently treated by transcatheter aortic valve implantation (TAVI) using the latest generation self-expandable transcatheter heart valve (THV) (Boston Scientific Acurate neo, size M [Boston Scientific, Marlborough, Massachusetts, United States]). TAVI followed modified procedural protocol and sizing algorithm. THV implantation without prior balloon aortic valvuloplasty resulted in an adequate valve function without leakage. Conclusion This THV may be particularly well suited for TAVI subsequent to LVAD implantation if modified sizing and deployment considerations are appreciated.